Intrarater Reliability of Chest Expansion using Cloth Tape Measure Technique (Bangladesh Journal of Medical Science, 2012)
Objective: The Objective of this study was to determine the intrarater reliability of chest expansion at three different anatomical landmarks using a cloth tape measure among healthy peoples. Materials and Methods: 120 healthy male and female volunteers were evaluated on two occasions in different days. The measures   consisted of chest expansion measurement at axilla, fourth intercostals and xiphoid levels. The measurements   were taken in the standing position with the arms hanging sideways at all the three different anatomical landmarks. The test-retest reliability of the measurements was determined by intraclass correlation coefficient (ICC) and standard error of measurements (SEMs). Results: An acceptable reliability was determined  by ICC values greater than than 0.85 and SEMs less than 5%. The mean age of the subjects was 21.93 years. ICC of all measures ranged between 0.95 to 0.97 and SEMs were 1.9%, 1.8%, 1.5% at the axillary, fourth intercostals and xiphoid level respectively. Conclusions: The findings of this study suggested that, the cloth   tape measurement was reliable at all the three different anatomical landmarks of the chest wall. Therefore, this measurement technique could be used as an outcome measure for chest expansion in the management   of cardiorespiratory conditions. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12602 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12